Rationality, Relativism and the Human Sciences
VIII, 243 p.
Keywords: The Greater Philadelphia Philosophy Consortium was launched in the early eighties. It began during a particularly lean period in the American economy. But its success is linked as much to the need to be in touch with the rapidly changing currents of the philosophical climate as with the need to insure an adequately stocked professional community in the Philadelphia area faced, perhaps permanently, with the threat of increasing attrition. The member schools of the Consortium now include Bryn Mawr College, the University of Pennsylvania, Temple University, and Villanova University, that is, the schools of the area that offer advanced degrees in philosophy. The philosophy faculties of these schools form the core of the Consortium, which offers graduate students the instructional and library facilities of each member school. The Consortium is also supported by the associated faculties of other regional schools that do not offer advanced degrees - notably, those at Drexel University, Haverford College, La Salle University, and Swarthmore College - both philosophers and members of other departments as well as interested and professionally qualified persons from the entire region. The affiliated and core professionals now number several hundreds, and the Consortium's various ventures have been received most enthusiastically by the academic community. At this moment, the Consortium is planning its fifth year of what it calls the Conferences on the Philosophy of the Human Studies.